Everyday watercolor : learn to paint watercolor in 30 days - Rainey, Jenna, 1989- (California : Watson-Guptill, 2017)
"A contemporary paint-every-day watercolor guide that explores foundational strokes and patterns and then builds new skills upon the foundations over the course of 30 days to create finished pieces"--
Includes index.
Keywords: Watercolor painting -- Technique